FORMATION OF ORTHOGRAPHIC LITERACY OF UZBEK-SPEAKING 5TH-GRADE STUDENTS IN RUSSIAN LANGUAGE LESSONS - Norboboyev Sobir Sodikovich ,Ismoilov Odilbek Alisherovich (International Journal of Literature and Language Studies, 2026)
This article examines the methodological foundations and practical approaches to developing orthographic literacy among 5th-grade students in schools with the Uzbek language of instruction during Russian as a second language lessons. The transition to the secondary level of education involves a sharp increase in the volume of abstract vocabulary and complex grammatical structures, which exacerbates the interference from the native language. Based on the analysis of typical spelling errors and systemic typographical deviations, this study identifies the most challenging phonetic-orthographic zones, such as the spelling of unstressed vowels, voiced and voiceless consonants, and reduction processes. The article proposes an integrated system of structural exercises, contrastive analysis techniques, and differentiated tasks designed to minimize phonetic interference. The empirical data collected during pedagogical monitoring confirms that targeted contrastive work significantly improves spelling accuracy and stabilizes the development of secondary linguistic competence.